Nutritional status among primary school children in rural Sri Lanka; a public health challenge for a country with high child health standards - N. P. G. C. R. Naotunna; M. Dayarathna; H. Maheshi; G. S. Amarasinghe; V. S. Kithmini; M. Rathnayaka; L. Premachandra; N. Premarathna; P. C. Rajasinghe; G. Wijewardana; T. C. Agampodi; S. B. Agampodi (BMC, 2017)
Abstract Background Nutritional status of pre adolescent children is not widely studied in Sri Lanka. The purpose of this study was to determine the nutritional status among pre-adolescent school children in a rural province of Sri Lanka. Methods A school based cross sectional study was carried out in North Central Province in 100 rural schools, selected using multi stage cluster sampling with probability proportionate to size. Children in grade one to five were enrolled with a maximum cluster size of fifty. Anthropometric measurements were done by trained data collectors and venesection was done at site by trained nurses. WHO AnthoPlus was used to calculate the BMI, height for age and weight for age Z scores. Survey design adjusted prevalence estimates with linearized standard errors were generated using svy function of STATA. Mean haemoglobin concentration (Hb) was calculated using methaeamoglobin method. Screening for iron deficiency and thalassemia trait was done using peripheral blood films. Results Height and weight measurements were done for 4469 of children and the Hb data was available for 4398 children. Based on the survey design adjusted estimates, prevalence of severe thinness, thinness, overweight and obesity in this population was 8.60% (SE 0.94), 2.91%(SE 0.74), 2.95%(0.26) and 2.43%(SE 0.92) respectively. Similarly, survey design adjusted prevalence of underweight and stunting were, 25.93% (95% CI 24.07-27.89%) and 43.92%(95% CI 40.55-47.56%). Adjusted mean estimates for hemoglobin was 12.20 (95% CI 12.16-12.24) g/dL. Prevalence of anemia was 17.3% (n = 749). Prevalence of mild and moderate anemia was 9.4 and 7.6% respectively. Conclusion This study confirms that malnutrition is still a major problem in North Central Province, Sri Lanka.